TUC Delegation to Germany, 1945 (1945)
1945 "TUC Delegation to Germany, 1945" [HFR0124], 1945 In November 1945, a TUC delegation visited Germany to report and advise on the re-establishment of free trade unions. The delegation comprised Will Lawther, Jack Tanner, H. Bullock, E.P. Harries and Albert Carthy. The delegation toured the Ruhr and Rhineland, meeting former trade union organisers who had been in hiding or in concentration camps during the war. This photo shows [left behind table] H. Bullock and Will Lawther speaking to Herr Derek, Oberburgermeister of Bonn in Dusseldorf.